Cytotoxicity analysis of three Bacillus thuringiensis Subsp. israelensis d-Endotoxins towards insect and mammalian cells - Corrêa, Roberto Franco Teixeira (2012)
Three members of the d-endotoxin group of toxins expressed by Bacillus thuringiensis subsp. israelensis, Cyt2Ba, Cry4Aa and Cry11A, were individually expressed in recombinant acrystalliferous B. thuringiensis strains for in vitro evaluation of their toxic activities against insect and mammalian cell lines. Both Cry4Aa and Cry11A toxins, activated with either trypsin or Spodoptera frugiperda gastric juice (GJ), resulted in different cleavage patterns for the activated toxins as seen by SDS-PAGE. The GJ-processed proteins were not cytotoxic to insect cell cultures. On the other hand, the combination of the trypsinactivated Cry4Aa and Cry11A toxins yielded the highest levels of cytotoxicity to all insect cells tested. The combination of activated Cyt2Ba and Cry11A also showed higher toxic activity than that of toxins activated individually. When activated Cry4Aa, Cry11A and Cyt2Ba were used simultaneously in the same assay a decrease in toxic activity was observed in all insect cells tested. No toxic effect was observed for the trypsin-activated Cry toxins in mammalian cells, but activated Cyt2Ba was toxic to human breast cancer cells (MCF-7) when tested at 20 mg/mL.